Examining recorded oral test as a test accommodation in measuring Orang Asli pupils’ mathematics performance - Suheysen, Revindran (2025)
The mathematics performance of Orang Asli pupils is commonly affected by language and literacy barriers. Introducing test accommodations may potentially serve as a solution to alleviate these issues faced by the pupils. This study employed a mixed-method approach to examine the use of recorded oral tests in the language of instruction and ethnic language as test accommodations on complex linguistic features such as item length and vocabulary. The quantitative approach of this study evaluated the mathematics performance of 142 Year 4 Orang Asli pupils from the Temiar ethnic group from seven primary schools in the states of Perak and Kelantan. To evaluate the effectiveness of the test accommodation, three mathematics tests comprising 40 test items were developed, which are a written test in Bahasa Melayu, recorded oral test in Bahasa Melayu, and recorded oral test in Bahasa Temiar. The quantitative data was analysed using ANOVA test and Pearson correlation. For the qualitative approach, content analysis was carried out on vocabulary type, while thematic analysis on semi-structured interviews with seven mathematics teachers were conducted to explore their views on the use of the recorded oral test for the Orang Asli pupils. Findings showed that the pupils performed significantly better when administered recorded oral tests, compared to the written test. Moreover, between the recorded oral tests, the findings indicated that pupils performed better when administered the test in Bahasa Melayu, compared to Bahasa Temiar. Three key themes were identified from the qualitative input, namely factors affecting pupils’ performance pre-test accommodation, support for post-recorded oral test accommodation, and future challenges on the use of recorded oral test. This study underscores the practical implementation of recorded oral test to reduce cognitive load caused by linguistic features as a fair and inclusive test accommodation in mathematics testing for Orang Asli pupils in Malaysia.